The bioliq® Entrained‐Flow Gasifier – A Model for the German Energiewende. Issue 4 (17th June 2020) - Eberhard, Mark; Santo, Ulrike; Michelfelder, Bernd; Günther, Armin; Weigand, Peter; Matthes, Jörg; Waibel, Patrick; Hagenmeyer, Veit; Kolb, Thomas
Abstract: The bioliq® process was developed at the Karlsruhe Institute of Technology (KIT) for the production of synthetic fuels from dry biomass residues. Biofuels of high quality are produced sustainably in various process steps. This multistage process not only considers the necessity for decentralized supply of the biomass, but also the necessity for a large centralized fuel synthesis that benefits from economy of scale. The entire process chain of pyrolysis, gasification, gas cleaning, and synthesis is operated on a pilot scale at KIT. The high‐pressure entrained‐flow gasifier converts the biomass, pretreated in a fast pyrolysis step, into a synthesis gas for the production of gasoline in the subsequent synthesis step. The first experimental results from the pilot plant are presented in this paper. Abstract : The bioliq® process produces synthetic fuels from dry biomass residues. The concept is to decentralize energy concentration to make the transport of biomass over longer distances economically meaningful. The process chain consists of pyrolysis, gasification, gas purification, and synthesis. First experimental results from high‐pressure entrained‐flow gasifiers are presented in this manuscript.